Answers

The Brainliest Answer!
2014-12-25T11:27:17+05:30

u=c/v Also, u= (lambda)/ lambda'

therefore c/v= lambda/lambda'

v/c=lambda'/ lambda

Hence v=(lambda'/lambda) x c

v=4500/6000 x 3 x 10^8 m/s

v= 2.25 x 10^8m/s


2 5 2
  • Brainly User
2014-12-25T11:31:45+05:30
We have a relation, \frac{Velocity_{medium-1}}{Velocity_{medium-2}}=\frac{Wavelength_{medium-1}}{Wavelength_{medium-2}} → Snell's Law.

From this, Velocity_{water}}=(Velocity_{air})\frac{Wavelength_{water}}{Wavelength_{air}}

Substitute them, you get Velocity_{water}}=(2.25)10^{8} m/s
2 5 2